HUBUNGAN STATUS GIZI DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS TOMPASO KABUPATEN MINAHASA - Tary melasri giroth; Jeanette I. Ch Manoppo; Hendro J. Bidjuni (Universitas Sam Ratulangi, 2022)
Backgropund: Developmental problems in children in Indonesia and in developing countries are generally caused by two things, namely poor nutritional conditions and infectious diseases. The high number of Upper Respiratory Tract Infection (URTI) is caused by one of the factors that must also be known by the public is the nutritional status including malnutrition. Aime: This study aims to find the correlation between of nutritional status with the incidence of ispa in toddlers in the tompaso health center of minahasa regency. Method: This research used quantitative with a cross sectional approach. Sampling in this study using the Purposive Sampling method obtained the number of samples as many as 62 respondents. The study was conducted by calcilating of z-score nutritional status of toddlers according to WHO and according to health professional assesment. The data analyzed using the Chi-square test. Results: The results of the study based on the characteristics of nutritional status obtained 30 toddlers have good nutritional status, 12 toddlers were over-nourished , 11 toddlers were obese, and 9 toddlersÂ were malnourished. Then, there were 32 toddlers who were experiencing URTI and there were 30 toddlers who did not or had previously experienced URTI. Data analysis showed p = 0.003 < = 0.05. Â Conclusion: this study concluded Â there was a relationship between nutritional status and the incidence of URTI in children under five at the Tompaso Public Health Center, Minahasa Regency.Keywords: Nutritional Status; Upper Respiratory Tract Infection; Toddler.